Status of Children from Unregistered Marriage Based on Minister of Home Affairs Regulation No. 109 of 2019 (Study of the Barru Regency Capil Population Service) - Suhera; Agus Muchsin; Zainal Said; Sudirman; Saidah (Universitas Muhammadiyah Palu, 2024)
Children are the most precious gift of marriage, and their physical and spiritual rights and needs must be met. Based on existing laws and regulations, the state recognizes and guarantees these rights by providing a birth certificate as proof and legal recognition. Marriages must be registered in accordance with Law Number 1 of 1974 which regulates marriage as a condition for registering the birth of a child. Therefore, knowing the status of children resulting from unregistered marriages is important and procedures for registering the birth of children resulting from unregistered marriages provide legal certainty. 1) What is the substance of Minister of Home Affairs Regulation Number 109 of 2019 regarding children resulting from unregistered marriages. 2) What factors influence the status of children who are not registered in the Minister of Home Affairs Regulation Number 109 of 2019 Capil Barru Regency. 3). How to Legally Settle Children Resulting from Unregistered Marriages Minister of Home Affairs Regulation Number 109 of 2019 Study of the Barru Regency Capil Population Service. This type of research is field research which is carried out in the middle of the research object in order to find out and obtain clear data using qualitative description methods. Research carried out in the field examines problems of a qualitative nature. The data collected is generally in the form of words, pictures and number books. The data collection uses observation, interview and documentation techniques, by analyzing the data using data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that the condition of children born from marriages that are not registered means that there is no authentic evidence that the child was born from a valid marriage. Based on the results of interviews with Barru Regency Capil employees, unregistered marriages result in difficulties in the process of obtaining certificates for children. Therefore, every marriage must be registered in order to provide full legal certainty and justice in the fulfillment of children's rights.